Don't kiss the frog! : princess stories with attitude - Waters, Fiona (New York : Kingfisher, 2013)
A collection of six stories about princesses who are anything but ordinary princesses.
Clumsy princess / Lou Kuenzler ; illustrated by Miriam Latimer -- Princess exchange / Anne Marie Ryan ; illustrated by Sarah Massini -- Princess and the P.E. / Angela Kanter ; illustrated by Miriam Latimer -- Sleepy beauty / William Bedford ; illustrated by Ella Burfoot -- Double dragons / Enid Richemont ; illustrated by Sarah Massini -- Princess Rose / Elaine Canham and Rose Canham ; illustrated by Ella Burfoot.
School Library Journal, November 2008.
4.7
K-3
R
Keywords: Princesses -- Juvenile fiction; Children's stories, English; Princesses -- Fiction; Short stories; Short stories; Humorous stories; Fairy tales -- Adaptations; Short stories